PENGARUH KOMPENSASI DAN DISIPLIN KERJATERHADAP KINERJA KARYAWAN PADA PEGADAIAN CABANG TIGARAKSA TANGERANG - Nurhadi, Nurhadi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Efforts made by the management of PT Pegadaian Tigaraksa branch in terms of policy, especially the compensation variable X1 and work discipline X2, the performance of Y employees at the Tigaraksa branch pawnshop, Tangerang. Research). The data analysis technique used in this study used date instrument test analysis, multiple linear regression test, correlation test, determination test, t test and f test by testing compensation and work discipline variables on employee performance at the Tigaraksa branch of pawnshops, Tangerang. Results of the research distribution of 100 populations absorbed by statistical analysis, namely a significant value of 0.000 <0.05, the H1 decision is accepted, so it can be concluded that there is a significant relationship between the effect of compensation and work discipline on employee performance at the Tigaraksa branch of pawnshops, Tangerang, obtained from a correlation coefficient value of 0.59, meaning quite strong, the coefficient of determinant between the effect of compensation and work discipline on employee performance at the pawnshop branch of Tigaraksa Tangerang contributes 68% while the remaining 32% is influenced by other variables not included in this study. The multiple regression equation formed is significant between the variables of the effect of compensation and work discipline on employee performance at the Tigaraksa branch pawnshop, Tangerang, of Y = 41,520 + 040 + 034, the significance value (sig) is 0.000 <0.05, so F count 2.24 > 3.44. then Ho is rejected and Ha is accepted, meaning accepted, in the multiple regression equation test formed between the effect of compensation and work discipline on employee performance at branch the Tigaraksa, Tangerang